A multi-degree of freedom piezoelectric vibration energy harvester with piezoelectric elements inserted between two nearby oscillators. (February 2016) - Xiao, Han; Wang, Xu; John, Sabu
Abstract: A novel piezoelectric vibration energy harvesting system is proposed whose harvesting performance could be significantly enhanced by introducing one or multiple additional piezoelectric elements placed between every two nearby oscillators. The proposed two degree-of-freedom piezoelectric vibration harvester system is expected to extract 9.78 times more electrical energy than a conventional two degrees of freedom harvester system with only one piezoelectric element inserted close to the base. A parameter study of a multiple degree-of-freedom piezoelectric vibration energy harvester system has been conducted to provide a guideline for tuning its harvesting bandwidth and optimizing its design. Based on the analysis method of the two degrees of freedom piezoelectric vibration harvester system, a generalised MDOF piezoelectric vibration energy harvester with multiple pieces of piezoelectric elements inserted between every two nearby oscillators is studied. The harvested power values of the piezoelectric vibration energy harvesters of 1 to 5 degree-of-freedom have been compared while the total mass and the mass ratio of the oscillators are kept as constants. It is found that the greater numbers of degree-of-freedom of a PVEH with the more additional piezoelectric elements inserted between every two nearby oscillators would enable that system to harvest more energy. The first mode resonant frequency will be shifted to a low-frequency range when the numbers of degree-of-freedom increase. Highlights: The proposed two degree of freedom piezoelectric vibration energy harvester could generate 9.78 times energy than that of a conventional two degree of freedom piezoelectric vibration energy harvester. The improvements of harvesting performance can be achieved with minor modification to the system. A comparison of piezoelectric vibration energy harvesters from one degree of freedom to five degree of freedom has been conducted. A generalized multiple degree of freedom piezoelectric vibration energy harvesting model is presented for parameter study and dimensionless analysis.